Population ecology of golden eagles (Aquila chrysaetos) using remote cameras - Ludovico Aoki Dahlén, Andressa (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
The golden eagle populations have been studied across their range but basic demographic information is missing for a large part of their range. As an apex predator and scavenger, eagles are essential to the ecosystems they inhabit. In this study I analyzed pictures from installed camera traps around eagle nests in six counties in Sweden. In 2017 and 2018 a total of 182,249 pictures were taken by 53 cameras. The project aims to establish demographic parameters for the Swedish golden eagle population. In my visual analyses I extracted 20 variables that were important to my aims. In order to do so I created two groups for the young: Chick1 (the older) and Chick2 (the younger). I used this classification to estimate productivity, chick survival, fledging age and timing. The monitoring of chicks started at a minimum median age of 33 days and a maximum of 73, within the Chick1 with a mean(±sd) value 52(±12) days and Chick2 52(±6) days. The average day of the year to fledging was day 200 (in Julian day) which is equivalent to the 18ᵗʰ July for Chick1 and day 199 which is equivalent to the 19ᵗʰ July for Chick2. The chicks fledged with a minimum age of 71 days and a maximum of 96 days within the mean(±sd) fledging age value of 84(±6) days for Chick1 and 85(±5) days for Chick2. The survival rate among the monitored chicks was 0.952 (+ 0329 and 95% CI 0.890 – 1) with only two known losses.